Adsorpsi Zn dan Dekolorisasi Limbah Batik Menggunakan Limbah Baglog Pleurotus ostreatus dengan Sistem Inkubasi dan Volume Limbah Batik Berbeda - Tjan Herwinda Kartikasari; Sri Lestari; Ratna Stia Dewi (Fakultas Biologi | Universitas Jenderal Soedirman, 2012)
Batik industry is one of the traditional textile industry in Indonesia which produce wastewater. Pollutants that contained in wastewater such as heavy metal and dyes. White rot fungi (Pleurotus ostreatus) from spent mushroom known can adsorb heavy metal and can decolorize dyes in wastewater. Spent mushroom have potential as an adsorbent because it still contains mycelium and cellulose. The purpose of this research is to know the difference of incubation system and volume of waste batik for adsorption Zn and decolorization by spent mushroom of P. ostreatus and the most optimal treatment adsorb Zn and decolorize waste batik. This research used experimental methods in Completely Randomized Design (CRD) with a split plot design. The main parameters observed were the value is the level of metal Zn and absorbance of waste batik. Data were analyzed by analysis of variance (F test) then proceed with a test of Honestly Significant Difference with an error rate of 1% and 5%. The result is spent mushroom of P. ostreatus able to adsorb Zn and to decolorize waste batik. The highest Zn adsorption is J2S treatment (62,406%) that was contained 75 ml indigosol green at static incubation. The highest decolorization is J1S treatment (77,991%) that was contained 50 ml indigosol green at static incubation.